THE COMPARISON OF SERVICE QUALITY OF DOMESTIC AIRLINES IN TURKEY - Onut, Semih; Akbas, Seyfettin; Yilmaz, Gokhan (YILDIZ TECHNICAL UNIV, 2007)
In this study airline service quality of domestic lines in Turkey is evaluated. Service quality can be considered as a composite of different attributes. There are also many criteria one should consider as part of the appropriate evaluation process of the service quality, including reliability, performance, responsibility, etc. Consequently evaluation procedures involve several objectives and it is often necessary to compromise among possibly conflicting tangible and intangible factors. For these reasons, multiple criteria decision making (MCDM) has been found to be a useful approach to solve this kind of problem. Analytical hierarchy process, one of the MCDM methods, is used for determining the weights of the selection criteria and evaluating service quality of domestic airlines in Turkey.
Keywords: Service quality; airlines; analytic hierarchy process (AHP); Engineering